Thermodynamic modeling of the Al-K system - Du Y.; Yuan X.; Sun W.; Hu B. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A thermodynamic modeling for the Al-K system is conducted. The thermodynamic parameters for liquid, (Al), and (K) are evaluated by using the experimental phase diagram data from the literature. The gas phase is described with an ideal gas model. The calculated Al-K phase diagram agrees well with the experimental data. In particular, the observed monotectic reaction is well described by the present calculation.